Comparative Analysis of Renewable Energy Policy Frameworks in South Asia: Lessons for Pakistan (Journal of Asian Development Studies, 2025)
As a South Asian region with 1.8 billion people, its rapid economic growth is increasing its energy requirements. Achieving this demand in conjunction with mitigating climate change can be effectively accomplished through renewable energy sources. This research analyses the renewable energy policies of India, Bangladesh, Nepal, and Sri Lanka. All countries demonstrated progress on the renewable energy front but the Shewhart analysis indicated there are still large differences present in the institutional structures, policies, incentives, and overall approaches to the policy. This research study will help provide constructs and best practices for Pakistan to improve its RE policy framework. This research places importance on establishing strict targets that are challenging to achieve, making funds available, and improving institutional capacity. The clean energy strategies will ensure that energy security is delivered while also meeting the country's plans for renewable energy deployment.